Economic empowerment through Kaaps - van der Rheede, Christo (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
As a regional variety, Kaaps can be seen as a driver of social, cultural, educational and economic interaction in specific contexts. However, the economic value of Kaaps and its role in economic empowerment in these contexts have not yet been properly researched. This chapter aims to inspire scholars to do in-depth research on the role that Kaaps already plays in the regional economy, as well as the role it can play as principal driver of many other commercial and artistic projects.